2020
DOI: 10.1007/s12264-020-00589-1
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Grained Topography and Modularity of the Macaque Frontal Pole Cortex Revealed by Anatomical Connectivity Profiles

Abstract: The frontal pole cortex (FPC) plays key roles in various higher-order functions and is highly developed in non-human primates. An essential missing piece of information is the detailed anatomical connections for finer parcellation of the macaque FPC than provided by the previous tracer results. This is important for understanding the functional architecture of the cerebral cortex. Here, combining cross-validation and principal component analysis, we formed a tractography-based parcellation scheme that applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 106 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…Second, according to Snyder's hope theory, hope is a general disposition through which one engages in a conscious effort to achieve goals and which includes their ability to create feasible routes toward aspirations and their belief that they are motivated to initiate or maintain progress toward a goal (Snyder, 2002). Evidence from the literature has indicated that FPC contributes to many aspects of cognition (e.g., goal‐directed cognition) (He et al., 2020; Hosoda et al., 2020). FPC's signal could promote learning on which types of goals and goal‐generating processes produce particular benefits, thereby improving future choices (Tsujimoto et al., 2011); this aspect corresponds to the planning function of trait hope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, according to Snyder's hope theory, hope is a general disposition through which one engages in a conscious effort to achieve goals and which includes their ability to create feasible routes toward aspirations and their belief that they are motivated to initiate or maintain progress toward a goal (Snyder, 2002). Evidence from the literature has indicated that FPC contributes to many aspects of cognition (e.g., goal‐directed cognition) (He et al., 2020; Hosoda et al., 2020). FPC's signal could promote learning on which types of goals and goal‐generating processes produce particular benefits, thereby improving future choices (Tsujimoto et al., 2011); this aspect corresponds to the planning function of trait hope.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study argues that hope is linked to amplitude of low‐frequency fluctuation (ALFF)/fractional ALFF (fALFF) in FPC, a subdivision of the prefrontal cortex (PFC) associated with problem‐solving, planning, and executive functions (Hosoda et al., 2020; Raju et al., 2021). Evidence from previous research has supported that the FPC plays a key role in several higher order functions, including goal‐directed persistence, prospection of future events, and decision‐making (He et al., 2020; Hosoda et al., 2020), corresponding to the hope theory of planning to meet goals (Snyder, 2002). Further, the extant literature has proposed that the FPC is inversely associated with decision impulsivity and risky decision‐making (Lv et al., 2020), which are negatively correlated with an individual's achievement of long‐term goals.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the conventional parcellation scheme (Li et al, 2017 ; He et al, 2020 ; see Figure 1b ), TCst of all voxels of SN were used to calculate a connection matrix (number of voxels of SN, VNsn × number of voxels of striatum and thalamus, VNst) and then a cross‐correlation matrix (VNsn × VNsn). The ( i , j )th element of the cross‐correlation matrix denotes the correlation between TCst maps of voxel i and j (i.e., lines i and j in the connection matrix).…”
Section: Methodsmentioning
confidence: 99%
“…For each subject, the connectivity profile of one component or subregion was only focused on the ipsilateral hemisphere and transformed into the CIVM space. To further reduce the false positive connections, 3.08  10 -5 for the samples (He et al 2020) was used to binarize the connectivity profile. We averaged connectivity profiles of the subregion across the subjects to get the probabilistic connectivity profile, and the threshold 0.5 was used to obtain the group-level connectivity profile for the given subregion.…”
Section: Sc Patternmentioning
confidence: 99%